Microalgal Co-Cultivation Prospecting to Modulate Vitamin and Bioactive Compounds Production - Luigi Pistelli; Angelo Del Mondo; Arianna Smerilli; Federico Corato; Concetta Piscitelli; Paola Pellone; Dora Allegra Carbone; Clementina Sansone; Christophe Brunet (Antioxidants, 2021)
Microalgal biotechnology is gaining importance. However, key issues in the pipeline from species selection towards large biomass production still require improvements to maximize the yield and lower the microalgal production costs. This study explores a co-cultivation strategy to improve the bioactive compounds richness of the harvested microalgal biomass. Based on their biotechnological potential, two diatoms (Skeletonema marinoi, Cyclotella cryptica) and one eustigmatophyte (Nannochloropsis oceanica) were grown alone or in combination. Concentrations of ten vitamins (A, B1, B2, B6, B12, C, D2, D3, E and H), carotenoids and polyphenols, together with total flavonoids, sterols, lipids, proteins and carbohydrates, were compared. Moreover, antioxidant capacity and chemopreventive potential in terms inhibiting four human tumor-derived and normal cell lines proliferation were evaluated. Co-cultivation can engender biomass with emergent properties regarding bioactivity or bioactive chemical profile, depending on the combined species. The high vitamin content of C. cryptica or N. oceanica further enhanced (until 10% more) when co-cultivated, explaining the two-fold increase of the antioxidant capacity of the combined C. cryptica and N. oceanica biomass. Differently, the chemopreventive activity was valuably enhanced when coupling the two diatoms C. cryptica and S. marinoi. The results obtained in this pilot study promote microalgal co-cultivation as a valuable strategy aiming to boost their application in eco-sustainable biotechnology.